2013
DOI: 10.1371/journal.pone.0079182
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dextran Sodium Sulfate-Induced Inflammation and Colonic Tumorigenesis in Smad3−/− Mice with Dysregulated TGFβ

Abstract: There are few mouse models that adequately mimic large bowel cancer in humans or the gastrointestinal inflammation which frequently precedes it. Dextran sodium sulphate (DSS)-induces colitis in many animal models and has been used in combination with the carcinogen azoxymethane (AOM) to induce cancer in mice. Smad3 −/− mice are deficient in the transforming growth factor beta (TGFβ) signaling molecule, SMAD3, resulting in dysregulation of the cellular pathway most commonly affected in human colorectal cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…The intestine samples were fixed in 10% phosphate-buffered formalin, processed routinely for paraffin embedding, sectioned at 5 µm, and stained with hematoxylin and eosin. Sections of distal colon were evaluated based on adapted criteria of Corazza et al [14] and Seamons et al [15]. The histopathological score of lesions was partially scored (0-4 increasing severity) with some parameters, namely, (1) presence of tissue loss/necrosis, (2) severity of mucosal epithelial lesion, (3) inflammation, (4) extent 1 - the percentage of intestine affected in any manner, and (5) extent 2 - the percentage of intestine affected by the most severe lesion.…”
Section: Methodsmentioning
confidence: 99%
“…The intestine samples were fixed in 10% phosphate-buffered formalin, processed routinely for paraffin embedding, sectioned at 5 µm, and stained with hematoxylin and eosin. Sections of distal colon were evaluated based on adapted criteria of Corazza et al [14] and Seamons et al [15]. The histopathological score of lesions was partially scored (0-4 increasing severity) with some parameters, namely, (1) presence of tissue loss/necrosis, (2) severity of mucosal epithelial lesion, (3) inflammation, (4) extent 1 - the percentage of intestine affected in any manner, and (5) extent 2 - the percentage of intestine affected by the most severe lesion.…”
Section: Methodsmentioning
confidence: 99%
“…The intestine samples were fixed in 10% phosphate‐buffered formalin, processed routinely for paraffin embedding, sectioned at 5 μm and stained with haematoxylin and eosin. Longitudinal sections of distal colon were evaluated based on adapted criteria of Corazza (1999) and Seamons (2013) and colleagues . The histopathological score of lesions were partially scored (0–4 increasing severity) with some parameters, namely: (1) presence of tissue loss/necrosis, (2) severity of mucosal epithelial lesion, (3) inflammation, (4) extent 1 – the percentage of intestine affected in any manner and (5) extent 2 – the percentage of intestine affected by the most severe lesion.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, increased cell proliferation as measured by two markers, correlated with the degree of inflammation. The potential complexity of the contribution of inflammation to tumor production is further highlighted in a recent paper (27) that reported that tumor production in Smad3 −/− mice was enhanced in Smad3 −/− ;Rag2 −/− mice (27). …”
Section: Resultsmentioning
confidence: 99%